Gene family expansions and contractions are associated with host range in plant pathogens of the genus Colletotrichum. (December 2016) - Baroncelli, Riccardo; Amby, Daniel; Zapparata, Antonio; Sarrocco, Sabrina; Vannacci, Giovanni; Le Floch, Gaétan; Harrison, Richard; Holub, Eric; Sukno, Serenella; Sreenivasaprasad, Surapareddy; Thon, Michael
Abstract Background Many species belonging to the genusColletotrichum cause anthracnose disease on a wide range of plant species. In addition to their economic impact, the genusColletotrichum is a useful model for the study of the evolution of host specificity, speciation and reproductive behaviors. Genome projects ofColletotrichum species have already opened a new era for studying the evolution of pathogenesis in fungi. Results We sequenced and annotated the genomes of four strains in theColletotrichum acutatum species complex (CAsc), a clade of broad host range pathogens within the genus. The four CAsc proteomes and secretomes along with those representing an additional 13 species (sixColletotrichum spp. and seven other Sordariomycetes) were classified into protein families using a variety of tools. Hierarchical clustering of gene family and functional domain assignments, and phylogenetic analyses revealed lineage specific losses of carbohydrate-active enzymes (CAZymes) and proteases encoding genes inColletotrichum species that have narrow host range as well as duplications of these families in the CAsc. We also found a lineage specific expansion of necrosis and ethylene-inducing peptide 1 (Nep1)-like protein (NLPs) families within the CAsc. Conclusions This study illustrates the plasticity ofColletotrichum genomes, and shows that major changes in host range are associated with relatively recent changes in gene content.